Pengaruh Green Accounting, Leverage, dan Profitabilitas terhadap Nilai Perusahaan dengan CSR Sebagai Variabel Moderasi - Maharani, Amanah Putri; Mustika, Ira Grania; Heniwati, Elok (Jurnal Edukasi (Ekonomi, Pendidikan dan Akuntansi), 2025)
The purpose of this study is to examine how corporate social responsibility moderates the impact of green accounting, leverage, and profitability on firm value. Mining businesses were sampled for this study, and the IDX provided data for the years 2019-2023. This study tests the validity of pre-existing hypotheses by utilizing panel data regression analysis as well as Eviews 12 software. The study findings illustrate that firm value is positively affected by green accounting. Meanwhile, firm value is not affected by profitability or leverage. Corporate social responsibility can influence green accounting and profitability on firm value. Meanwhile, leverage cannot be moderated by corporate social responsibility on firm value.